2016
DOI: 10.1080/15548627.2016.1190071
|View full text |Cite
|
Sign up to set email alerts
|

Atg5-mediated autophagy deficiency in proximal tubules promotes cell cycle G2/M arrest and renal fibrosis

Abstract: Macroautophagy/autophagy protects against cellular stress. Renal sublethal injury-triggered tubular epithelial cell cycle arrest at G 2 /M is associated with interstitial fibrosis. However, the role of autophagy in renal fibrosis is elusive. Here, we hypothesized that autophagy activity in tubular epithelial cells is pivotal for inhibition of cell cycle G 2 /M arrest and subsequent fibrogenic response. In both renal epithelial cells stimulated by angiotensin II (AGT II) and the murine kidney after unilateral u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 39 publications
5
145
0
1
Order By: Relevance
“…The formation of autophagosome is a key point in the process of autophagy, and once autophagy is induced, isolation of double membrane emerges to coat cargo and then elongates and expands to form the autophagosome . Beclin1 and ATG5 are necessary autophagy‐related proteins for the formation of double membrane; the conversion of endogenous LC3 I to LC3 II and exogenous GFP‐LC3 puncta is typically characterized as an autophagosome marker . Here, we found that Beclin1 and ATG5 protein levels were upregulated, and conversion of endogenous LC3 I to LC3 II and GFP‐LC3 puncta significantly increased in hippocampus neurons treated with DNLA, suggesting strongly that DNLA promotes autophagosome formation.…”
Section: Discussionmentioning
confidence: 78%
“…The formation of autophagosome is a key point in the process of autophagy, and once autophagy is induced, isolation of double membrane emerges to coat cargo and then elongates and expands to form the autophagosome . Beclin1 and ATG5 are necessary autophagy‐related proteins for the formation of double membrane; the conversion of endogenous LC3 I to LC3 II and exogenous GFP‐LC3 puncta is typically characterized as an autophagosome marker . Here, we found that Beclin1 and ATG5 protein levels were upregulated, and conversion of endogenous LC3 I to LC3 II and GFP‐LC3 puncta significantly increased in hippocampus neurons treated with DNLA, suggesting strongly that DNLA promotes autophagosome formation.…”
Section: Discussionmentioning
confidence: 78%
“…On the one hand, it has been shown that in proximal epithelial cells, ATG5-mediated autophagy reduced type I collagen deposition by blocking the G 2 /M phase arrest (42), a cell cycle phase whose arrest would initiate DNA repair and synthesis of pro-fibrotic factors (43). Furthermore, bleomycin-induced pulmonary fibrosis in a mouse model led to increased autophagy activation in the lungs as revealed by upregulated ATG5 protein expression levels and increased autophagosome formation (44).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Livingston et al showed that renal fibrosis in obstructed kidneys was ameliorated in renal proximal tubule Atg7-knockout mice and interesting, this was associated with decreased production of specific pro-fibrotic factors 130 . However, Li et al reported higher levels of renal fibrosis in obstructed kidneys of proximal tubule Atg5-knockout mice 131 . Thus, while the protective role of autophagy in AKI is well-established, it is inconclusive whether autophagy is beneficial or detrimental to kidney repair.…”
Section: Potential Mechanisms Underlying the Susceptibility Andmentioning
confidence: 97%